Involvement of Exogenous N-Acyl-Homoserine Lactones in Spoilage Potential of Pseudomonas fluorescens Isolated From Refrigerated Turbot - Li, Tingting; Wang, Dangfeng; Ren, Likun; Mei, Yongchao; Ding, Ting; Li, Qiuying; Chen, Haitao; Li, Jianrong (Frontiers in Microbiology, 2019)
Some bacteria can modulate their spoilage potential by responding to environmental signaling molecules via the quorum sensing (QS) system. However, the ability of Pseudomonas fluorescens, the specific spoilage organism (SSO) of turbot, to response to environmental signaling molecules remains unclear. This study investigated the effects of six synthetic N-acyl homoserine lactones (AHLs) on typical behaviors mediated by QS in P. fluorescens, such as biofilm formation and extracellular protease activity. Total volatile basic nitrogen (TVB-N) was used as a spoilage indicator to evaluate quality changes in AHL-treated turbot filets during storage. The results confirm the enhancing effect of environmental AHLs on QS-dependent factors of P. fluorescens and quality deterioration of turbot filets, with C4-HSL and C14-HSL being the most effective. Moreover, the content decrease of exogenous AHLs was also validated by gas chromatography–mass spectrometry analysis. Further, changes in rhlR transcription levels in P. fluorescens suggest that this bacterium can sense environmental AHLs. Finally, molecular docking analysis demonstrates the potential interactions of RhlR protein with various exogenous AHLs. These findings strongly implicate environmental AHLs in turbot spoilage caused by P. fluorescens, suggesting preservation of turbot should not exclusively consider the elimination of SSO-secreted AHLs.